MENENTUKAN DEVIASI DARI HIMPUNAN TERURUT PARSIAL - Amir, Amir Kamal (MATEMATIKA, 2009)
To measure of how close the ring is to being Artinian ring is used usually so called Krull dimention. In the case of noncommutative rings, the Krull dimention is measured on the lattice of ideals. In this situation, the lattice ofÂ  ideals is seen as a poset (partial orderedÂ  set) and then the deviation of the poset is measured. This paper will describe, completely, deviation of posets including the deviation of product of two posets. Moreover, this paper also will present characteristic of poset which has a deviation and does not have. Â